2015
DOI: 10.1371/journal.pone.0144839
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Impact of School Closure on the Transmission Dynamics during the Pandemic Flu H1N1-2009 in Oita, Japan

Abstract: BackgroundSchool closure is considered as an effective measure to prevent pandemic influenza. Although Japan has implemented many class, grade, and whole school closures during the early stage of the pandemic 2009, the effectiveness of such a school closure has not been analysed appropriately. In addition, analysis based on evidence or data from a large population has yet to be performed. We evaluated the preventive effect of school closure against the pandemic (H1N1) 2009 and examined efficient strategies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 25 publications
1
51
0
4
Order By: Relevance
“…This rule is applied not only to elementary schools but also to children’s day care centers, nursing schools, junior high schools, and high schools. Then those schools must report the number of absent students diagnosed with influenza as well as closures (class, grade, or school) to the local Education Board in each municipality [34]. …”
Section: National Influenza Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…This rule is applied not only to elementary schools but also to children’s day care centers, nursing schools, junior high schools, and high schools. Then those schools must report the number of absent students diagnosed with influenza as well as closures (class, grade, or school) to the local Education Board in each municipality [34]. …”
Section: National Influenza Surveillancementioning
confidence: 99%
“…In many cases, a class is closed when the number of absences due to ILI exceeds 10–20 %. Several groups evaluated the most optimal duration of class closure, and it was suggested that school closure lasting more than 4 or 5 days is effective to mitigate the spread of influenza [34–37]. …”
Section: National Influenza Surveillancementioning
confidence: 99%
“…A large body of literature exists on the closure of educational institutions to reduce the spread of infectious disease in the community by breaking important chains of transmission [12][13][14]. In light of rising concern about the current COVID-19 pandemic, a growing number of universities across the world have either postponed or canceled all campus events such as workshops, conferences, sports (both intra and inter universities), and other activities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous pieces of literature showed the closure of educational institutions as an effective strategy for breaking the critical transmission chain during the pandemic (Earn et al, 2012;Kawano & Kakehashi, 2015;Luca et al, 2018;Wu et al, 2010). Still, it has negative consequences on students' academic study, including learning interruptions, disruption to assessment, and the impact is more severe on students from disadvantaged backgrounds (UNESCO, 2020a).…”
Section: Introductionmentioning
confidence: 99%